Research progress on the correlation between type Ⅱ inflammatory cytokines and pemphigus - Shuqiong YOU; Fuqiong JIANG; Qian WU; Ruiting HUANG; Lingyu HU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Pemphigus is a chronic autoimmune bullous skin disease that affects the skin and/or mucous membranes. The pathogenesis of pemphigus is closely associated with the formation of autoantibodies against desmoglein, involving B cell-mediated humoral immunity and T cell-mediated cellular immunity. Cytokines play a role in the immune response. Therefore, it is of great importance to explore the role of cytokines in the pathogenesis of pemphigus. This article reviews the association of Th2 cells and their cytokines, including IL-4, IL-5, IL-6, IL-10, IL-13 and IL-31, with the onset of pemphigus, thereby unraveling the pivotal role of type Ⅱ inflammatory responses in the pathogenesis of pemphigus.